Aktualisasi Diri Calon Guru Bahasa Inggris Dalam 21st Century Learning - Agnes Siwi Purwaningtyas (JLA (Jurnal Lingua Applicata), 2017)
Language teaching in the 21st century should accommodate various skills that must be acquired by the students which include skills to analyze and solve problems, create and innovate, think critically, collaborate, and communicate. Language teachers should also integrate information and communication technology in the learning process to improve the quality of learning instruction and help to reach those learning goals. Addressing these challenges, teachers as well as teacher candidates need to develop their qualities and keep updating their knowledge. Teaching training program in the university therefore offer courses and programs to improve the competence and skills of the teacher candidates. English Program of Vocational College of Universitas Gadjah Mada also offer similar training although it is not extensively implemented since it only covers the introductory foundation for language teaching.  Nevertheless, the students successfully demonstrate their teaching potentials and self-actualize themselves as teachers. The results of questionnaire, observation, and reflection show that the teacher candidates actualize their potentials as decision maker, designer, manager, learning facilitator, motivator, as well as creative, reflective, technology-literate, self-efficacious, and communicative teacher.